Doctor Patient Type of Language Used and Tuberculosis Treatment Adherence in Kibera Informal Settlement in Nairobi County, Kenya - Koech, Beatrice; Sikolia, Geoffrey; Macharia, Nancy (Journal of Health, Medicine and Nursing, 2024)
Purpose: To explore the type of language used on tuberculosis treatment adherence in an informal settlement in Nairobi County, Kenya. Methodology: This was by a descriptive qualitative research design. The sample size was 67 and comprised 10 healthcare workers and 57 TB patients. Purposive sampling technique was used to sample the participants. The study conducted 37 unstructured in-depth interviews and 3 focus group discussions. Data analysis was conducted by first translating the data, then transcribing the verbatim of the in-depth unstructured interviews and focus group discussions. The transcribed data was later analyzed using thematic analysis. Data was presented using tables, bar charts and pie charts. Findings: The findings of the study indicated that majority of the tuberculosis patients found that the type of language used by the healthcare workers when communicating with them determined whether they would adhere to treatment or not. If the language used was not well understood by the patient or if the healthcare worker used complex language, then the patient was not likely to adhere to treatment. The findings further indicated that more than half of the patients were fluent in Swahili language while the remaining patients only had basic knowledge of the language. Sixty percent that is 34 of the participants were fluent in Swahili language whereas thirty- eight percent that is 22 patients had basic knowledge of the language, and one did not understand the language and opted to communicate with the help of an interpreter. Seventy percent that is 40 of the patients indicated that when the healthcare workers communicated with them in simple language they were more likely to adhere to TB treatment. Findings from the healthcare workers indicated that Swahili was the preferred language used by both the healthcare workers and the tuberculosis patients. If a patient did not understand Swahili language, the healthcare workers would look for an interpreter who would then translate to the patient the required information. The use of complex medical language was only used when the healthcare workers were communicating amongst themselves. Unique Contribution to Theory and Practice and Policy: The constructs of the theories informed the study in terms of treatment adherence by emphasizing the benefits of seeking healthcare early. On practice, healthcare workers needed to be aware of type of language used when interacting with their patients as they are likely to affect their patients' adherence to treatment. Based on these findings, policymakers should ensure that all healthcare workers should use simple language that is, the use of plain common words to make it easier for the patients to understand. In addition, any health messages, appointment cards or any other TB information whether spoken or written meant for the patients, should be designed in a language that is simple for the patient to comprehend.